Cardiovascular disease preventive medication dispensing for almost every New Zealander 65 years and over: a preventive treatment paradox?. (23rd January 2022) - Wells, Sue; Choi, Yeunhyang; Jackson, Rod; Parwaiz, Mariam; Mehta, Suneela; Selak, Vanessa; Harwood, Matire; Grey, Corina; Kerse, Ngaire; Poppe, Katrina
Abstract: Objective: To describe the dispensing of cardiovascular disease (CVD) preventive medications among older New Zealanders with and without prior CVD or diabetes. Methods: New Zealanders aged ≥65 years in 2013 were identified using anonymised linkage of national administrative health databases. Dispensing of blood pressure lowering (BPL), lipid lowering (LL) or antithrombotic (AT) medications, was documented, stratified by age and by history of CVD, diabetes, or neither. Results: Of the 593, 549 people identified, 32% had prior CVD, 14% had diabetes (of whom half also had prior CVD) and 61% had neither diagnosis. For those with prior CVD, between 79–87% were dispensed BPL and 73–79% were dispensed AT medications, across all age groups. In contrast, LL dispensing was lower than either BPL or AT in every age group, falling from 75% at age 65–69 years to 43% at 85+ years. For people with diabetes, BPL and LL dispensing was similar to those with prior CVD, but AT dispensing was approximately 20% lower. Among people without prior CVD or diabetes, both BPL and AT dispensing increased with age (from 39% and 17% at age 65–69 years to 56% and 35% at 85+ years respectively), whereas LL dispensing was 26–31% across the 65–84 year age groups, falling to 17% at 85+ years. Conclusion: The much higher dispensing of BPL and AT compared to LL medications with increasing age suggests a preventive treatment paradox for older people, with the medications most likely to cause adverse effects being dispensed most often.